Identification of Functional Amino Acid Residues Involved in Polyamine and Agmatine Transport by Human Organic Cation Transporter 2 - Higashi, Kyohei (Public Library of Science, 2014)
Polyamine (putrescine, spermidine and spermine) and agmatine uptake by the human organic cation transporter 2 (hOCT2) was studied using HEK293 cells transfected with pCMV6-XL4/hOCT2. The Km values for putrescine and spermidine were 7.50 and 6.76 mM, and the Vmax values were 4.71 and 2.34 nmol/min/mg protein, respectively. Spermine uptake by hOCT2 was not observed at pH 7.4, although it inhibited both putrescine and spermidine uptake. Agmatine was also taken up by hOCT2, with Km value: 3.27 mM and a Vmax value of 3.14 nmol/min/mg protein. Amino acid residues involved in putrescine, agmatine and spermidine uptake by hOCT2 were Asp(427), Glu(448), Glu(456), Asp(475), and Glu(516). In addition, Glu(524) and Glu(530) were involved in putrescine and spermidine uptake activity, and Glu(528) and Glu(540) were weakly involved in putrescine uptake activity. Furthermore, Asp(551) was also involved in the recognition of spermidine. These results indicate that the recognition sites for putrescine, agmatine and spermidine on hOCT2 strongly overlap, consistent with the observation that the three amines are transported with similar affinity and velocity. A model of spermidine binding to hOCT2 was constructed based on the functional amino acid residues.